2018
DOI: 10.1016/j.jspd.2017.06.006
|View full text |Cite
|
Sign up to set email alerts
|

The True Ponte Osteotomy: By the One Who Developed It

Abstract: Level IV, therapeutic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 12 publications
2
48
0
1
Order By: Relevance
“…Rahimizadeh et al (17) reviewed 68 cases of C-OLF resulting in progressive quadriparesis and demonstrated that C-OLF rarely leads to cervical myeloradiculopathy. Different imaging techniques have different advantages in the diagnosis of disease (18). MRI may reveal hypertrophy of the ligamentum flavum and compression of the spinal cord in the cervical spine (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rahimizadeh et al (17) reviewed 68 cases of C-OLF resulting in progressive quadriparesis and demonstrated that C-OLF rarely leads to cervical myeloradiculopathy. Different imaging techniques have different advantages in the diagnosis of disease (18). MRI may reveal hypertrophy of the ligamentum flavum and compression of the spinal cord in the cervical spine (18).…”
Section: Discussionmentioning
confidence: 99%
“…Different imaging techniques have different advantages in the diagnosis of disease (18). MRI may reveal hypertrophy of the ligamentum flavum and compression of the spinal cord in the cervical spine (18). The causes of OLF in the cervical spine remain to be elucidated (19).…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, correction was done using spine-to-rod method. 21,24 The anatomically contoured titan rods were inserted in the heads of pedicle screws to correct the primary curve. Finally, after tightening the rods to screws' heads, a Stagnara 25 wake-up test was performed to evaluate the neurological function of the patients.…”
Section: Methodsmentioning
confidence: 99%
“…All the structural major and minor curves were fused while non-structural compensatory curves were not included. For 10 patients with xed deformity, multiple Ponte osteotomies [15] were used to attain correction via a posterior approach. Curve correction was achieved using the direct vertebral derotation maneuver, followed by slight convex compression and concave distraction.…”
Section: Surgical Proceduresmentioning
confidence: 99%